Endoscopic Endonasal Transsphenoidal Approach to Sellar Lesions: A Detailed Account of Our Mononostril Technique - Linsler, Stefan; Gaab, Michael Robert; Oertel, Joachim (Journal of Neurological Surgery Part B: Skull Base, 2013)
Objective The endonasal endoscopic approach is currently under investigation for perisellar tumor surgery. A higher resection rate is to be expected and nasal complications should be minimized. Here, the authors report their technique of transnasal endoscopic neurosurgery after 218 procedures.Methods Between October 2000 and September 2011, 210 patients received 218 endoscopic endonasal transsphenoidal procedures for perisellar lesions. Procedures were video recorded. The surgical technique was carefully analyzed. These cases were prospectively followed.Results Standard technique was mononostril approach with 0-degree optics. 30-degree and—after availability—45-degree optics were used for assessment of radicality. On follow-up, magnetic resonance imaging revealed radical tumor resection in 94 out of 104 cases (90.3%). Recurrent tumor growth was observed in five younger patients (2.2%). There was no mortality and a low complication rate. Three patients (1.4%) complained postoperatively of nasal congestion or reduced nasal air flow; however, no complaints were considered to be severe.Conclusion In comparison with other literature reports, the results are comparable or even better with respect to surgical radicality. The very low rate of nasal complaints is particularly remarkable. The technique has been shown to be safe and successful with a high radicality and only minor complications.
Keywords: endoscopy; mononostril; endonasal transsphenoidal approach; sellar lesions